Strategi TK Sholeh Arrahman dalam Meningkatkan Keterampilan Motorik Kasar Anak (Studi Kasus di TK Sholeh Arrahman-Mangunjaya) - Ai Teti Wahyuni; Siti Ulfah Quraesin; Ahmad Firlii Sapputra (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Children's gross motor development includes balance and coordination between body parts. However, low gross motor skills in children are due to the average child being less able to coordinate hand and foot movements perfectly. This study aims to describe strategies in developing children's gross motor skills with data collection techniques using observation, interviews, documentation with research subjects at Sholeh Arrahman Kindergarten in group A aged (4-5 years) with a total of fifteen children. The research was conducted using a qualitative descriptive method. As a result, the teacher's role as an educator is the basis of success with the development of children's gross motor skills, starting from introducing, giving examples, motivating, directing, evaluating to competing for the traditional jumping rope game activity. Based on the results of research in group A in Sholeh Arrahman Kindergarten with fifteen children as research subjects. In the indicator of jumping with one leg there are twelve children who are classified as good category, and three children who are classified as sufficient category. In the indicator of jumping with two legs together there are fifteen children who are classified as very good category. In the indicator of children jumping with a height of 20cm-40cm, there are twelve children who are classified as good category and three children who are classified as sufficient category. In the indicator that children can maintain body balance, there are fifteen children who are classified as very good. In the indicator that children can jump with various variations, there are twelve children who are classified as good category and three children who are classified as sufficient category. In the strategy of using conventional learning strategies it worked well.